(untitled) (The Review of Diabetic Studies, 2025)
Workforce shortages and workload pressures have become persistent global issues affecting hospital healthcare systems, with significant implications for patient care, staff wellbeing, and organizational sustainability. Healthcare professionals in physical therapy, radiology, health services administration, nursing, and medicine are among the most impacted by increasing clinical demand and insufficient staffing resources. This review examines current evidence on the causes, consequences, and system-level effects of workforce shortages and workload burden among hospital healthcare staff. The review highlights the multifactorial nature of the problem, including demographic shifts, staffing models, administrative inefficiencies, inadequate training pipelines, increased patient acuity, and high rates of burnout. The Methods section describes the literature search strategy, followed by Results that synthesize findings regarding staffing deficits, mental health impact, operational challenges, patient safety concerns, and economic implications. The Discussion section integrates these findings and proposes organizational and policy-level recommendations targeting recruitment, workforce planning, workflow optimization, and mental health support for hospital staff. The review concludes that addressing workforce shortages and workload burden requires coordinated, evidence-driven strategies across educational, organizational, and governmental systems to achieve long-term resilience in hospital care delivery.